Android Stagefright vulnerability threatens all devices – and fixing it isn't that easy. (August 2015) - Unknown
Abstract : A flaw found in all currently used versions of the Android operating system can potentially give an attacker control over the device simply by sending it a maliciously crafted multimedia message.